2000
DOI: 10.1111/0161-4681.00088
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cross-Race Dyad Partnerships in Learning to Teach

Abstract: This three-year study examined ways in which race mediates the process of learning to teach. The innovation of pairing racial minority and dominant group teacher candidates in field-based practica was based on the rationale that such collaboration would enrich the pedagogical process with different perspectives, traditions, resources, and experiences from which teacher candidates, associate teachers, and students would benefit. The findings revealed that such partnerships broke down some racial barriers, tackl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…This provides a space for understanding the multiple knowledges and understandings that are present within any social landscape. Solomon (2002) has effectively employed the cross-race dyad approach in which students of different racial groups are paired during their placements. This paring serves many purposes.…”
Section: Implications For Teacher Education For a Racially Diverse Somentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a space for understanding the multiple knowledges and understandings that are present within any social landscape. Solomon (2002) has effectively employed the cross-race dyad approach in which students of different racial groups are paired during their placements. This paring serves many purposes.…”
Section: Implications For Teacher Education For a Racially Diverse Somentioning
confidence: 99%
“…4. See Solomon's (2002) work on cross-race dyad system that provides the structure for candidates of different racial groups to collaborate and be mutually supportive in their communities of practice. 5.…”
Section: Implications For Teacher Education For a Racially Diverse Somentioning
confidence: 99%
“…We chose to focus on responses to this question because of knowledge gained from supervising candidates in their practicum where we observed that the associate teacher's attitude often determined the candidates' overall experiences. The fact that these associate teachers determine whether the candidates pass or fail the practicum component of the programme adds stress to an already challenging situation (for a detailed description of the role of the teacher associates see, for example Allen, 2008;Dlamini & Martinovic, 2007;Solomon, 2000).…”
Section: The Meaning Of 'Good'mentioning
confidence: 99%
“…41 While shared interests created the foundation for the participants' collaboration, the cohort dynamic was enhanced by the diversity of the students in the PRSE program. 42 This appreciation for diversity encompassed everything from ethnicity to sexual orientation to areas of academic interest. The participants felt that the variety of perspectives that was represented in the program challenged them to think more deeply about the challenges that they faced in the classroom.…”
Section: The Teacher Learning Questionmentioning
confidence: 99%